Advancing Formulation Development with AI: ANN-Driven Modeling and Optimization of Etodolac Extended-Release Tablets - Paritosh Kunwar Singh; Vinay Kumar; Ashish Parihar; Gauri Goyal; Suruchi Singh; Pankaj Bhatt (Journal of Pharmaceutical Innovation, 2026)

Genetic transformation of rice (Oryza sativa L.) plants with the Hsp101 genomic fragment containing the coding sequence and its natural, heat-inducible promoter produced transgenics with enhanced heat tolerance - Lisha Khungar; Gayatri Tripathi; Mohit Kumar Swarnkar; Tanya Biswas; Kumar Paritosh; Anil Grover (Plant Science, 2026)

A heavy-tailed model for multivariate spatial processes - Paritosh Kumar Roy; Alexandra M. Schmidt (Spatial Statistics, 2026)

AI-Powered Predictive Modeling to Optimize Pharmaceutical Formulation and Precise Drug Delivery in Modified Release Tablets - Paritosh Kunwar Singh; Vinay Kumar; Ashish Parihar; Kamal Shah; Hitesh Kumar Dewangan (Journal of Pharmaceutical Innovation, 2026)

Enhanced decolorization of congo red and methyl orange using Bacillus haynesii ING6: an optimization study using central composite design (CCD) - Isha Dharsandia; Narendra Kumar; Ananya Tiwari; Paritosh Parmar (Biodegradation, 2025)

Inactivation of Vaccinia Virus via Nitric Oxide‐Plasma Activated Water: A Potential Way to Inactivate Mpox Virus - Paritosh Patel; Tirtha Raj Acharya; Sudakshya S. Lenka; Soujanya Ghosh; Subhadip Mukherjee; Prajwal Lamichhane; Apurva Jaiswal; Suresh K. Verma; Neha Kaushik; Eun Ha Choi; Nagendra Kumar Kaushik (Journal of Hazardous Materials, 2025)

Integrative biomonitoring in Litopenaeus vannamei: Metal analysis and biochemical markers - Neeraj Kumar; Paritosh Kumar; Raju Baitha; Dilip Kumar Singh; Kotha Sammi Reddy (Marine Pollution Bulletin, 2025)

Optimizing mechanical and durability properties of recycled aggregate concrete using pozzolanic slurries and modified mixing approach - Paritosh Kumar Singh; Puja Rajhans (European Journal of Environmental and Civil Engineering, 2024)

Magical role of iron nanoparticles for enhancement of thermal efficiency and gene regulation of fish in response to multiple stresses - Neeraj Kumar; Paritosh Kumar; Kotha Sammi Reddy (Fish & Shellfish Immunology, 2024)

Amplification of avian influenza virus circulation along poultry marketing chains in Bangladesh: A controlled field experiment - Lisa Kohnle; Tridip Das; Md. Helal Uddin; Sanjib Chandra Nath; Md. Abu Shoieb Mohsin; Rashed Mahmud; Paritosh Kumar Biswas; Md. Ahasanul Hoque; Dirk Udo Pfeiffer; Guillaume Fournié (Preventive Veterinary Medicine, 2024)

Biocompatible plasma-treated liquids: A sustainable approach for decontaminating gastrointestinal-infection causing pathogens - Manorma Negi; Neha Kaushik; Prajwal Lamichhane; Apurva Jaiswal; Shweta B. Borkar; Paritosh Patel; Prashant Singh; Eun Ha Choi; Nagendra Kumar Kaushik (Journal of Hazardous Materials, 2024)

Surface air gas discharge plasma: An ecofriendly virus inactivation approach to enhance CPRRs mediated antiviral genes expression against airborne bio-contaminant (human Coronavirus-229E) - Paritosh Patel; Neha Kaushik; Tirtha Raj Acharya; Eun Ha Choi; Nagendra Kumar Kaushik (Environmental Pollution, 2024)

Influence of treated recycled concrete aggregate and modified mixing approach on the mechanical properties of ternary blend geopolymer concrete: Experiments and machine learning algorithms - Paritosh Kumar Singh; Puja Rajhans (Journal of Cleaner Production, 2024)

In vivo molecular biocompatibility of Calotropis gigentea contrived smart Poly(N-isopropylacrylamide)-co-sulphonic-Silver microgel hybrid with embryonic Danio rerio inferred via intrinsic atomic physiological impacts - Ealisha Jha; Paritosh Patel; Puja Kumari; Krishn Kumar Verma; Pritam Kumar Panda; Priti S. Mohanty; Swadheena Patro; Rajender S. Varma; Yogendra Kumar Mishra; Nagendra Kumar Kaushik; Mrutyunjay Suar; Suresh K. Verma (Journal of Environmental Chemical Engineering, 2023)

Synergistic degradation of Chlorpyrifos by modified solar Photo-Fenton process with bacterial metabolism reduces in vivo biotoxicity in zebrafish (Danio rerio) - Tanmaya Nayak; Paritosh Patel; Aishee Ghosh; Faizan Zarreen Simnani; Khushbu Kumari; Sourav Das; Aditya Nandi; Arpan Ghosh; Pritam Kumar Panda; Nagendra Kumar Kaushik; Vishakha Raina; Suresh K. Verma (Science of The Total Environment, 2023)

Genome-wide identification and functional analysis of denitrosylases (S-nitrosoglutathione reductases and NADPH-dependent thioredoxin reductases) in Brassica juncea - Priyanka Babuta; Kumar Paritosh; Renu Deswal (Plant Biotechnology Reports, 2023)

Zebrafish-based platform for emerging bio-contaminants and virus inactivation research - Paritosh Patel; Aditya Nandi; Suresh K. Verma; Neha Kaushik; Mrutyunjay Suar; Eun Ha Choi; Nagendra Kumar Kaushik (Science of The Total Environment, 2023)

Reactor physics calculation and measurement during first approach to criticality of Apsara-U research reactor - Tej Singh; Paritosh Pandey; Jainendra Kumar; Shantanab Banerjee (Annals of Nuclear Energy, 2023)

Hypoxia Induces Early Neurogenesis in Human Fetal Neural Stem Cells by Activating the WNT Pathway - Devanjan Dey; Vadanya Shrivastava; Diksha Joshi; Chitra Mohinder Singh Singal; Sagar Tyagi; Muzaffer Ahmed Bhat; Paritosh Jaiswal; Jai Bhagwan Sharma; Jayanth Kumar Palanichamy; Subrata Sinha; Pankaj Seth; Sudip Sen (Molecular Neurobiology, 2023)

Genomic selection for spot blotch in bread wheat breeding panels, full-sibs and half-sibs and index-based selection for spot blotch, heading and plant height - Philomin Juliana; Xinyao He; Jesse Poland; Krishna K. Roy; Paritosh K. Malaker; Vinod K. Mishra; Ramesh Chand; Sandesh Shrestha; Uttam Kumar; Chandan Roy; Navin C. Gahtyari; Arun K. Joshi; et al. (Theoretical and Applied Genetics, 2022)
Key message Genomic selection is a promising tool to select for spot blotch resistance and index-based selection can simultaneously select for spot blotch resistance, heading and plant height. Abstract A major biotic stress challenging bread wheat production in regions characterized by humid and warm weather is spot blotch caused by the fungus Bipolaris sorokiniana . Since genomic selection (GS) is a promising selection tool, we evaluated its potential for spot blotch in seven breeding panels comprising 6736 advanced lines from the International Maize and Wheat Improvement Center. Our results indicated moderately high mean genomic prediction accuracies of 0.53 and 0.40 within and across breeding panels, respectively which were on average 177.6% and 60.4% higher than the mean accuracies from fixed effects models using selected spot blotch loci. Genomic prediction was also evaluated in full-sibs and half-sibs panels and sibs were predicted with the highest mean accuracy (0.63) from a composite training population with random full-sibs and half-sibs. The mean accuracies when full-sibs were predicted from other full-sibs within families and when full-sibs panels were predicted from other half-sibs panels were 0.47 and 0.44, respectively. Comparison of GS with phenotypic selection (PS) of the top 10% of resistant lines suggested that GS could be an ideal tool to discard susceptible lines, as greater than 90% of the susceptible lines discarded by PS were also discarded by GS. We have also reported the evaluation of selection indices to simultaneously select non-late and non-tall genotypes with low spot blotch phenotypic values and genomic-estimated breeding values. Overall, this study demonstrates the potential of integrating GS and index-based selection for improving spot blotch resistance in bread wheat.

Antecedents and consequences of adopting CLTS among tribal communities to become open defecation free: case study on Indian Swachh Bharat Abhiyan - Amit Adlakha; Paritosh Pathak; Anup Kumar; Prashant Pandey (Environmental Science and Pollution Research, 2022)

Functional Diversity of the Excretory/Secretory Proteins of Nematode Parasites - Paritosh Joshi; Prasanta Kumar K. Mishra (Acta Parasitologica, 2022)

Characterization of five new pathotypes of Puccinia triticina identified from Northeast India, Nepal, and Bangladesh - Subodh Kumar; Subhash Chander Bhardwaj; Om Prakash Gangwar; Pramod Prasad; Ranjana Chakrabarty; Prem Lal Kashyap; Hanif Khan; Siddanna Savadi; Baidya Nath Mahato; Paritosh Kumar Malaker (Australasian Plant Pathology, 2022)

Curse of La Corona: unravelling the scientific and psychological conundrums of the 21st century pandemic - Arpit Shukla; Paritosh Parmar; Gitanjali Kapoor; Dweipayan Goswami; Chaitanya Kumar Jha; Baldev Patel; Meenu Saraf (Molecular Diversity, 2022)

Isolation and antimicrobial resistance of motile Salmonella enterica from the poultry hatchery environment - Shafayat Zamil; Jinnat Ferdous; Mosammat Moonkiratul Zannat; Paritosh Kumar Biswas; Justine S. Gibson; Joerg Henning; Md. Ahasanul Hoque; Himel Barua (Veterinary Research Communications, 2021)

Solid state anaerobic digestion of water poor feedstock for methane yield: an overview of process characteristics and challenges - Kunwar Paritosh; Vinod Kumar; Nidhi Pareek; Dinabandhu Sahoo; Yadira Bajon Fernandez; Frederic Coulon; Tanja Radu; Nupur Kesharwani; Vivekanand Vivekanand (Waste Disposal & Sustainable Energy, 2021)

Evaluation of elite bread wheat lines for resistance to blast disease in Bangladesh - Krishna Kanta Roy; Md Mostofa Ali Reza; Md Muzahid-E-Rahman; Md Babul Anwar; Kishowar-E-Mustarin; Muhammad Rezaul Kabir; Paritosh Kumar Malaker; Naresh Chandra Deb Barma; Md Israil Hossain; Xinyao He; Aakash Chawade; Pawan Kumar Singh (Euphytica, 2021)

First report of barley blast caused by Magnaporthe oryzae pathotype Triticum (MoT) in Bangladesh - Krishna Kanta Roy; Md Mostofa Ali Reza; Md Muzahid-E-Rahman; Kishowar E. Mustarin; Paritosh Kumar Malaker; Naresh Chandra Deb Barma; Xinyao He; Pawan Kumar Singh (Journal of General Plant Pathology, 2021)

Enhancing the Stability of Haemonchus contortus Glyceraldehyde-3-Phosphate Dehydrogenase and Binding of Host Albumin to the Parasite Enzyme - Yapu Nijo; Prasanta Kumar K. Mishra; Paritosh Joshi (Acta Parasitologica, 2020)

Characterization of a 66 kDa Secretory Protein of Haemonchus contortus and Its Effect on Host Mononuclear Cells - Murugavel Sokkalingam; Amir Kumar Samal; Lakshmi Prasanth Thangavelu; Paritosh Joshi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Chromium removal efficiency of plant, microbe and media in experimental VSSF constructed wetlands under monocropped and co-cropped conditions - Paritosh Kumar; Ravinder Kaur; Defo Celestin; Prakash Kumar (Environmental Science and Pollution Research, 2020)

BjuWRR1, a CC-NB-LRR gene identified in Brassica juncea, confers resistance to white rust caused by Albugo candida - Heena Arora; K. Lakshmi Padmaja; Kumar Paritosh; Nitika Mukhi; A. K. Tewari; Arundhati Mukhopadhyay; Vibha Gupta; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2019)

Identification and characterization of the promoter of a gene expressing mainly in the tapetum tissue of cotton (Gossypium hirsutum L.) - Kumar Paritosh; Amarjeet Kumar Singh; Amita Kush Mehrotra; Deepak Pental; Pradeep Kumar Burma (Plant Biotechnology Reports, 2018)

Temperature induces lead toxicity in Pangasius hypophthalmus: an acute test, antioxidative status and cellular metabolic stress - N. Kumar; K. K. Krishnani; M. P. Brahmane; S. K. Gupta; Paritosh Kumar; N. P. Singh (International Journal of Environmental Science and Technology, 2018)

Modelling approaches for simulating wetland pollutant dynamics - Célestin Defo; Ravinder Kaur; Anshu Bharadwaj; Khajanchi Lal; Paritosh Kumar (Critical Reviews in Environmental Science and Technology, 2017)

Identification of genic SSRs and construction of a SSR-based linkage map in Brassica juncea - Namrata Dhaka; Arundhati Mukhopadhyay; Kumar Paritosh; Vibha Gupta; Deepak Pental; Akshay K. Pradhan (Euphytica, 2017)

Tetralocular ovary and high silique width in yellow sarson lines of Brassica rapa (subspecies trilocularis) are due to a mutation in Bra034340 gene, a homologue of CLAVATA3 in Arabidopsis - Satish Kumar Yadava; Kumar Paritosh; Priya Panjabi-Massand; Vibha Gupta; Atika Chandra; Y. S. Sodhi; Akshay K. Pradhan; Deepak Pental (Theoretical and Applied Genetics, 2014)

Structural and Transcriptional Characterization of rbcS Genes of Cotton (Gossypium hirsutum) - Kumar Paritosh; Deepak Pental; Pradeep Kumar Burma (Plant Molecular Biology Reporter, 2013)

Detrimental effect of expression of Bt endotoxin Cry1Ac on in vitro regeneration, in vivo growth and development of tobacco and cotton transgenics - Preeti Rawat; Amarjeet Kumar Singh; Krishna Ray; Bhupendra Chaudhary; Sanjeev Kumar; Taru Gautam; Shaveta Kanoria; Gurpreet Kaur; Paritosh Kumar; Deepak Pental; Pradeep Kumar Burma (Journal of Biosciences, 2011)